DISTRIBUSI TENAGA KESEHATAN DI INDONESIA: TINJAUAN SCOPING TERHADAP KETIMPANGAN DAN UPAYA PEMERATAAN DI DAERAH URBAN DAN REMOTE - Sheila Rizkia Anjari; Dumilah Ayuningtyas; Vetty Yulianty Permanasari (Jurnal Manajemen Kesehatan Indonesia, 2026)
Health workers are the spearhead of services in health facilities. WHO (Workforce 2030) states that many countries experience a concentration of health workers in urban areas and shortages in remote areas. Data from the Indonesian Ministry of Health 2023 shows that DKI Jakarta (urban) does not experience a shortage of doctors, dentists, nurses, and midwives (0%), while Papua Mountains (remote) experiences a significant shortage of doctors at 62.8%, dentists at 90.2%, nurses at 45.1%, and midwives at 72.6%. This indicates the need for policy analysis of the distribution of health workers between urban and remote areas. This study is a scoping review by analyzing articles from search results using PRISMA guidelines in the Scopus, PubMed, DOAJ, and Google Scholar databases. The results of this study indicate that the distribution of health workers in Indonesia is still uneven, with a concentration in urban areas and a significant shortage in remote areas. Efforts to achieve equality through various government policies such as the Healthy Archipelago and special assignments have been carried out, but their implementation has not been optimal in addressing inter-regional disparities, so data-based policies and sustainable strategies are needed to strengthen the distribution and retention of health workers in remote areas.Keywords: Health Workforce Distribution, Inequality, Policy, Remote, Urban.